2009
DOI: 10.1021/bc900214f
|View full text |Cite
|
Sign up to set email alerts
|

pH-Sensitive Radical-Containing-Nanoparticle (RNP) for the L-Band-EPR Imaging of Low pH Circumstances

Abstract: For the imaging of low pH circumstances in vivo, a pH-sensitive radical-containing-nanoparticle (RNP), which has an intense electron paramagnetic resonance (EPR) signal, was designed and developed using a self-assembling amphiphilic block copolymer (PEG-b-PCTEMPO) composed of a hydrophilic poly(ethylene glycol) (PEG) segment and a hydrophobic poly(chloromethylstyrene) (PCMS) segment in which the chloromethyl groups were converted to 2,2,6,6-tetramethylpiperidinyloxys (TEMPOs) via the amination of PEG-b-PCMS bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 34 publications
(43 reference statements)
6
80
0
Order By: Relevance
“…Before the effect of RNP on the transfection efficiency was evaluated, the interaction between RNP and the PEI/pDNA polyplex was investigated by electron spin resonance (ESR). We have already confirmed that the ESR spectra of RNP markedly change from a broad to sharp triplet due to the disintegration of RNP [20]. If RNP interacts with the PEI/pDNA polyplex, a change in the ESR spectra of RNP must be observed owing to the morphology change in RNP.…”
Section: Ros Scavenging Effect Of Rnp On Pei/pdna Gene Delivery Systemsupporting
confidence: 67%
See 3 more Smart Citations
“…Before the effect of RNP on the transfection efficiency was evaluated, the interaction between RNP and the PEI/pDNA polyplex was investigated by electron spin resonance (ESR). We have already confirmed that the ESR spectra of RNP markedly change from a broad to sharp triplet due to the disintegration of RNP [20]. If RNP interacts with the PEI/pDNA polyplex, a change in the ESR spectra of RNP must be observed owing to the morphology change in RNP.…”
Section: Ros Scavenging Effect Of Rnp On Pei/pdna Gene Delivery Systemsupporting
confidence: 67%
“…RNP was prepared following the methods of Yoshitomi et al [20]. An amphiphilic block copolymer possessing a poly(ethylene glycol) (PEG) chain as a hydrophilic segment and a polystyrene chain as a hydrophobic segment with TEMPO repeating units was prepared using two-step reactions.…”
Section: Synthesis Of Rnpmentioning
confidence: 99%
See 2 more Smart Citations
“…Core-shell-type polymeric micelles containing nitroxide radicals have already been developed for the treatment of oxidative stress injuries and in vivo ESR imaging [29,30]. It has been confirmed that they not only strongly scavenge ROS in vivo or in vitro but also significantly prevent oxidative stress damage in an cerebral ischemia-reperfusion injury model in rats [31], renal ischemia-reperfusion injury model in mice [32] and a neuron cell line used as a model for Alzheimer's disease [33,34], in which excess ROS is generated.…”
Section: Introductionmentioning
confidence: 99%